Teaching English in the shadow: identity construction of private English language tutors in China. Issue 1 (2nd January 2022) - Xiong, Tao; Li, Qiuna; Hu, Guangwei
ABSTRACT: The global spread of private tutoring of English (PTE) has become a driving force of the global marketisation of English. Drawing on critical discourse analysis, this study explores how tutors in the PTE sector, an under-researched group of teachers, construct their professional identities in the market-oriented educational, institutional, and socioeconomic settings. Findings show that they have constructed a range of hybrid identities, that is, tutors as exam experts, tutors as salespeople, and tutors as underdogs. These identities reflect multiple overlapping discourse in private supplementary tutoring (PST) underlined by the utilitarian discourse underlying exam-oriented education and the neoliberal discourse promoting the market logic of competition and profit-making. The instability and vulnerability of their identities have led to the tutors' deprofessionalisation and identity crisis. This paper also offers discussions on the space of shadow education and recommendations on policy making.